Surgical treatment of patients, suffering goiter with compressive syndrome - O. P. Kovalev; O. M. Liulka; V. І. Liakhovskyi; І. І. Nemchenko; A. V. Sydorenko (Клінічна хірургія, 2020)
Objective. To analyze the operative interventions character, performed in patients, suffering goiter of large size and cervico-retrosternal localization of thyroid gland with signs of compressive syndrome, and to determine preventive measures for prophylaxis of suboperative complications.